Tropics-wide intraseasonal oscillations - Jiawei Bao; Sandrine Bony; Daisuke Takasuka; Caroline Muller (Proceedings of the National Academy of Sciences, 2025)
The tropical climate variability is characterized by various oscillations across a range of timescales. Oscillations that imprint the tropical mean state are generally attributed to slow processes, such as the seasonal cycle or interannual variability. Here, we identify a pronounced tropics-wide intraseasonal oscillation (TWISO) in satellite observations and reanalyses. This oscillation, with a period of 30 to 60 d, is evident across multiple variables and involves interactions between convection, radiation, surface fluxes, and large-scale circulation. It is primarily manifested as convective perturbations in the tropical Indo-Pacific warm pool accompanied by oscillations in the large-scale tropical overturning circulation. Here, we examine the relationship between TWISO, the Madden–Julian Oscillation (MJO), and the instability of radiative-convective equilibrium. Certain phases of TWISO coincide with specific phases of the MJO, suggesting a potential connection between the two. However, although the MJO can amplify the oscillation amplitude of TWISO, it is not essential for TWISO to occur. Finally, due to its broad manifestation across the tropics, TWISO potentially exerts widespread influence on tropical weather and climate at regional scales.